BIOTECHNOLOGY AND BIOLOGICAL SCIENCES proceedings of the 3rd International Conference of Biotechnology and Biological Sciences (BIOSPECTRUM 2019), August 8-10, 2019, Kolkata, India ([S.l.] : CRC PRESS, 2019)
The application of Biotechnology dates back to the early era of civilization, when people first started to cultivate food crops. While the early applications are certainly still relevant, modern biotechnology is primarily associated with molecular biology, cloning and genetic engineering not only to increase the yield and to improve the quality of the crop but also its potential impact has touched upon virtually all domains of human interactions. Within the last 50 years, several key scientific discoveries revolutionized the biological sciences that facilitated the rapid growth of the biotechnology industry. 'Biotechnology and Biological Sciences III' contains the contributions presented at the 3rd International Conference on Biotechnology and Biological Sciences (BIOSPECTRUM 2019, Kolkata, India, 8-10 August 2019). The papers discuss various aspects of Biotechnology such as: microbial biotechnology, bioinformatics and drug designing, innovations in pharmaceutical industries and food processing industries, bioremediation, nano-biotechnology, and molecular-genetics, and will be of interest to academics and professionals involved or interested in these subject areas.
OCLC-licensed vendor bibliographic record.
Keywords: Biotechnology -- Congresses; MEDICAL / Biotechnology; SCIENCE / Biotechnology; SCIENCE / Life Sciences / Biology / General